Data governance value orders and jurisdictional conflicts - Obendiek, Anke Sophia (New York Oxford University Press, 2022)
"This book investigates the governance of digital data as a site of fundamental normative and political ordering processes that unfold in light of ever-increasing inter- and transnational linkages. Data governance is characterized by frequent jurisdictional overlap: Regulatory efforts in one jurisdiction will likely affect the conduct of others. How do different actors resolve overlapping claims? Existing literature has identified the impact of institutional processes and power struggles but has underestimated - and undertheorized - prevailing normative differences"--
1: Introduction: jurisdictional overlap in data governance-- 2: Theorizing the resolution of jurisdictional conflicts-- 3: Value orders and the genesis of the field of data governance-- 4: Safe harbour and its discontents: the Empowerment of individuals in the EU-- 5: Passenger data in air travel: establishing data as a security 'tool'-- 6: Financial data sharing: The extended arm of the US treasury-- 7: Access denied? struggles over electronic evidence-- 8: The right to be forgotten: moral hierarchies of fairness-- 9: Conclusion: normative visions across jurisdictional Conflicts
Includes bibliographical references (pages [229]-277 ) and index.
Keywords: Conflict of laws -- Data protection; Conflict of laws -- Law and legislation; Data protection -- Legal status, laws, etc